1998
DOI: 10.1001/jama.280.20.1764
|View full text |Cite
|
Sign up to set email alerts
|

Dose of Hemodialysis and Survival

Abstract: Context.-Although blacks receive lower doses of hemodialysis than whites, their survival when receiving dialysis treatment is better than that for whites. Previous studies of the relationship between the dose of dialysis and patient survival have not controlled for differences in patient characteristics.Objective.-To examine the association of mortality with the dose of hemodialysis for clusters of patients categorized by race and sex.Design.-Retrospective analysis of laboratory data and mortality outcomes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(35 citation statements)
references
References 21 publications
2
33
0
Order By: Relevance
“…Additional analyses showed that ‘dose-target bias' may be the reason of discrepancies [45]. Several studies showed that sex and body mass also influence the outcomes, and women and low-weight patients may benefit more from a higher dialysis dose [46,47,48,49]. So it is still difficult to find an optimal dialysis dose for HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additional analyses showed that ‘dose-target bias' may be the reason of discrepancies [45]. Several studies showed that sex and body mass also influence the outcomes, and women and low-weight patients may benefit more from a higher dialysis dose [46,47,48,49]. So it is still difficult to find an optimal dialysis dose for HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from the USA reported greater mortality for Caucasoid patients, particularly women, than for African-Americans [23], whereas women in the general population outsurvive men. On the other hand, there appears to be a survival advantage for the morbidly obese (BMI >35) haemodialysis patient whereas in the general population, the morbidly obese have increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The body composition of Caucasoids and African/Afro-Caribbean subjects was different, particularly for women. This may help explain, to some extent, some of the differences in mortality previously reported between different ethnic groups and sexes [23], as female Caucasoids are more likely to receive lower dialysis doses than Africans/Afro-Caribbean subjects. In addition to ethnic differences, we also noted changes with diabetes, again leading to increased body fat and loss of muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that 9 out of 14 studies reported lower all-cause mortality with greater serum prealbumin levels in hemodialysis (HD) patients (4). Cardiovascular mortality is also inversely associated with prealbumin levels (5, 6). It was also demonstrated that lower prealbumin concentrations were associated with mortality and hospitalization rates due to infection, independently of serum albumin.…”
Section: Introductionmentioning
confidence: 99%